Analisis Faktor Penyebab Kelainan Anak Berkebutuhan Khusus dan Implementasi Peran Guru dalam Pemenuhan Hak ABK - Putri Rahmadani; Roza Nurvadilah; Wahyu Bilhaq; Opi Andriani (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This research aims to identify the factors that cause abnormalities in children with special needs and implement the role of teachers in fulfilling the rights of children with special needs. The research method used is the literature review method or literature study to examine problems based on the topic being studied. Researchers obtained 10 books and journal articles combined in total. Where 4 books discuss the factors that cause abnormalities in children with special needs and 6 journal articles discuss the implementation of the role of teachers and fulfilling the rights of children with special needs. The results of the study show that there are several factors that cause ABK. These factors are divided into three periods of the child's life including: (1) Before birth: genetic disorders, pregnancy infections, maternal age during pregnancy, Poisoning During Pregnancy, Abortion, and Premature Birth. (2) During the birth process: Long birth process (Anoxia), premature birth, lack of oxygen, Birth with an assistive device or Vacuum, and Pregnancy too duration. (3) After birth: Bacterial infectious diseases (TB), Lack of nutrients (nutrition), Accidents to babies, and Poisoning Danger of poisoning (overdose). And the roles played by special education teachers are Pedagogical roles include teaching, providing assignment instructions, helping students focus on completing assignments, and conducting assessments. Non-pedagogical roles include helping self-management in managing the behavior of children with special needs, emotional support, consultation, and establishing communication with teachers, parents and students.